2022
DOI: 10.1177/00139165221129539
|View full text |Cite
|
Sign up to set email alerts
|

Communicating the Scientific Consensus on Climate Change: Diverse Audiences and Effects Over Time

Abstract: Prior research has demonstrated that communicating the scientific consensus that human-caused climate change is happening is an effective way to increase public understanding and engagement with the issue. However, less is known about (1) how persuasive this message is to oppositional audiences, (2) how long message effects last over time, and (3) what factors predict whether such effects last. We address these questions in a two-wave longitudinal study and find that consensus messaging leads to updated consen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 92 publications
0
14
1
Order By: Relevance
“…As such, for our purposes, this was useful and efficient given there was clearly an objectively right answer to this question (i.e., experts do agree). However, on other views, this kind of question might perhaps be better characterized as perceived expert consensus , since one’s response may also involve attitudinal elements (e.g., Goldberg et al, 2022; Lewandowsky et al, 2013). Accordingly, it may be prudent for future research to select multiple measures for key variables, preferably including psychometrically validated scales and instruments if available.…”
Section: Discussionmentioning
confidence: 99%
“…As such, for our purposes, this was useful and efficient given there was clearly an objectively right answer to this question (i.e., experts do agree). However, on other views, this kind of question might perhaps be better characterized as perceived expert consensus , since one’s response may also involve attitudinal elements (e.g., Goldberg et al, 2022; Lewandowsky et al, 2013). Accordingly, it may be prudent for future research to select multiple measures for key variables, preferably including psychometrically validated scales and instruments if available.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of climate change, evolution, or the origin of the universe, the answer is an unequivocal "yes." Moreover, Goldberg et al (2022) have shown acknowledge of what the scientific consensus on climate change is has a significant effect on individuals' beliefs, particularly among the doubtful or dismissive. In addition, this effect is shown to be enduring.…”
Section: Scientific Consensusmentioning
confidence: 99%
“…Second is an understanding of the social practices used by science to protect against error and produce reliable, trustworthy knowledge. As one example, studies demonstrate that teaching people about the scientific consensus on climate change can lead them to update their beliefs accordingly (e.g., Goldberg et al, 2022).…”
Section: What Can Be Done By Scientists and Science Educators To Deve...mentioning
confidence: 99%
See 1 more Smart Citation
“…Most empirical research on the impact of strategic messaging only measures effects immediately after the message (therefore not considering durability), artificially forces 100% reach in the audience of study participants (therefore not considering reach), and most does not consider the many restraining forces that exist in noisy, complex, and competitive real-world environments. Although there are notable exceptions to this paradigm (e.g., Allcott, 2011;Broockman & Kalla, 2016;Chong & Druckman, 2013;Gerber & Green, 2012;Goldberg et al, 2021;Goldberg et al, 2022;Gustafson et al, 2022;Kalla & Broockman, 2020;Maertens et al, 2020;Mousa, 2020;Paluck, 2009), they are relatively uncommon. The present framework highlights the importance of explicitly considering these elements in research and practice by explaining how the reach, durability, and restraining forces are just as essential as the campaign's "effect" in determining the true impact of a strategic communication campaign.…”
Section: Disclosure Statementmentioning
confidence: 99%